2016
DOI: 10.1371/journal.ppat.1005384
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic and Antiinflammatory Therapy Transiently Reduces Inflammation and Hypercoagulation in Acutely SIV-Infected Pigtailed Macaques

Abstract: Increased chronic immune activation and inflammation are hallmarks of HIV/SIV infection and are highly correlated with progression to AIDS and development of non-AIDS comorbidities, such as hypercoagulability and cardiovascular disease. Intestinal dysfunction resulting in microbial translocation has been proposed as a lead cause of systemic immune activation and hypercoagulability in HIV/SIV infection. Our goal was to assess the biological and clinical impact of a therapeutic strategy designed to reduce microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 86 publications
2
40
0
Order By: Relevance
“…In accordance with our previous studies in which two out of five SIVsab-infected PTMs were rapid progressors (49, 50), one animal out of three progressed to AIDS in the first 100 days postinfection in the untreated group, however, no rapid progression was registered in the Ixolaris group. Statistical significance was not reached in the present study, possibly due to the small sample size.…”
Section: Resultssupporting
confidence: 92%
“…In accordance with our previous studies in which two out of five SIVsab-infected PTMs were rapid progressors (49, 50), one animal out of three progressed to AIDS in the first 100 days postinfection in the untreated group, however, no rapid progression was registered in the Ixolaris group. Statistical significance was not reached in the present study, possibly due to the small sample size.…”
Section: Resultssupporting
confidence: 92%
“…Though mechanistic details have not yet been elucidated, our data suggest that incipient SIV infection compromises the integrity of the gastrointestinal epithelium, which led to our hypothesis that microbial translocation amplifies early immunodeficiency virus replication. Our hypothesis is supported by previous work[7,8,30,37,40] linking microbial exposure to increased plasma viremia and by our observation that a prolonged recrudescent viremia is provoked by short-course treatment of SIV-infected macaques with the gastrointestinal permeabilizing compound, DSS.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the level of sCD14, a marker of microbial translocation, increased in 5 of the 6 animals post-ABX in our study and remained elevated through 6 weeks post-FMT. Although we cannot conclude that these changes were solely induced by ABX due to the lack of an ABX-only control group, a recently published study with chronically infected pigtail macaques similarly observed an increase in sCD14 levels in 2 of the 3 animals after treatment with the antibiotic rifaximin and the anti-inflammatory agent sulfasalazine (49). To our knowledge, no other studies have assessed inflammatory cytokines after ABX in infected macaques.…”
Section: Discussionmentioning
confidence: 76%
“…Future FMT studies with macaques could also consider the use of prescreening of potential macaque donors to identify donor feces with a high microbial diversity or enriched for beneficial bacterial communities, the use of a combination of probiotics and fecal material, or the use of fecal material from healthy humans to better represent the human microbiota. Additionally, a recent report demonstrated that altering the microbiome with antibiotic treatment with a luminal antibiotic (rifaximin) together with an anti-inflammatory drug (sulfasalazine) during acute SIV infection resulted in beneficial reductions in immune activation and microbial translocation, while treatment during chronic infection had no discernible effect (49). This suggests that future studies assessing the benefits of FMT in lentiviral infection may result in increased benefits if it is administered during the acute phase of infection.…”
Section: Discussionmentioning
confidence: 99%